Illíria a francia nagyhatalmi politikában a 19. század elején - Vizi, László Tamás (Közép-Európai Közlemények, 2011)
With France’s declaration of war in 1792, a nearly fifteen year long war series started. Opened the new European power policy’s era, that restructured the international political relations. Paris initially strived to reach the natural borders, and their international recognition. After 1805 he openly seeking to acquire the leadership in Europe. The acquisition of the Illyrian providence in 1809 was part of this. Napoleon on the day of the signature of the Schonbrunn peace on 14th October 1809 established the Illyrian providence with imperial decree. The centre of the 55 km2large and 1.5 million inhabitants Illyrian providence was the Carniolan Laichbach. He appointed a governor general to be the head of the providence. Untill 1813, the existence of the Illyrian providence Illyria had four governor generals: Auguste Marmont, Henri Bertrand and Andoche Junot General, and Joseph Fouche, Napoleon’s former police Minister. The parts of the Illyrian providence were: the Villach centred Carinthia, the Austrian Istria that includes Triest and Gorze, the Laibach centred Carniola, Fiume and the Hungarian Primorje, the civil and armed Croatia, Dalmatia and the former Republic of Raguzai and Cattaro. The political reason of their establishment was Austria’s weakening, and the elimination of the Austrian-British relation. The geopolitical reason was the Italian Kingdom’s protection and a starting base to the Balkan. The economical reason was to provide the continental quarantine. The French Empire hold the Illyrian providence till 1813 autumn. However, after the defeat of Leipzig they couldn’t hold the providence. Four years after its establishment the French should give it up. In 1815, on the Congress of Vienna, they reannexed it to the Austrian Empire. We can say about the Illyrian providence that: It was born in the Wagram battle, was baptized in the Schonbrunn peace, died at the battle of nations, next to Leipzig, buried at the Congress of Vienna.